2009
DOI: 10.1186/cc8123
|View full text |Cite
|
Sign up to set email alerts
|

Electrical muscle stimulation preserves the muscle mass of critically ill patients: a randomized study

Abstract: IntroductionCritically ill patients are characterized by increased loss of muscle mass, partially attributed to sepsis and multiple organ failure, as well as immobilization. Recent studies have shown that electrical muscle stimulation (EMS) may be an alternative to active exercise in chronic obstructive pulmonary disease (COPD) and chronic heart failure (CHF) patients with myopathy. The aim of our study was to investigate the EMS effects on muscle mass preservation of critically ill patients with the use of ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
260
1
39

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(310 citation statements)
references
References 43 publications
10
260
1
39
Order By: Relevance
“…CT and MRI modalities have been shown to have an advantage over ultrasound in serial measurements, which is probably to relate to use of bony landmarks for measurement position in comparison to the use of surface anatomy. However, a randomised controlled trial using electrical muscle stimulation to reduce muscle wasting in the intensive care unit setting has shown that ultrasound measurement of the quadriceps has strong potential as a bedside imaging modality for identifying serial changes in muscle bulk following intervention [41].…”
Section: Significance Of the Findingsmentioning
confidence: 99%
“…CT and MRI modalities have been shown to have an advantage over ultrasound in serial measurements, which is probably to relate to use of bony landmarks for measurement position in comparison to the use of surface anatomy. However, a randomised controlled trial using electrical muscle stimulation to reduce muscle wasting in the intensive care unit setting has shown that ultrasound measurement of the quadriceps has strong potential as a bedside imaging modality for identifying serial changes in muscle bulk following intervention [41].…”
Section: Significance Of the Findingsmentioning
confidence: 99%
“…Несколько исследований группы греческих авторов [25][26][27] проводились у пациентов многопрофильного ОРИТ со значением оценки по шкале APACHE II более 13 баллов. В первом оценивали толщину мышечного слоя мускулатуры бедра после курса ЭСМ, который начинали со 2-х суток пребывания в ОРИТ до момента перевода в профильное отделение.…”
Section: клинические данные использования эсм в оритunclassified
“…В первом оценивали толщину мышечного слоя мускулатуры бедра после курса ЭСМ, который начинали со 2-х суток пребывания в ОРИТ до момента перевода в профильное отделение. У всех пациентов развивалась мы-шечная атрофия, однако в группе ЭСМ ее выраженность была значительно меньше как в абсолютных цифрах (-0,11±0,06 см против -0,21±0,10 см; p=0,009), так и в от-носительных значениях (-8,0±3,9% против -13,9±6,4%; p=0,005) [25]. В работе C. Routsi и соавт.…”
Section: клинические данные использования эсм в оритunclassified
See 1 more Smart Citation
“…Sabe-se que o treino de força no músculo reto abdominal através de dispositivos de expiração forçada, melhora o recrutamento de fibras, e consequentemente a tosse, mas existe uma série de condições clínicas e limitações que contraindica o uso destes para essa finalidade [16][17][18][19] . Além disso, já existem evidências que a eletroestimulação transcutânea em musculatura respiratória tem bons efeitos em pacientes crônicos, inclusive neurológicos, em quadros de atrofia muscular [20][21][22][23][24][25] . A aplicação da corrente Russa é feita com eletrodos de superfície na musculatura esquelética para fornecimento de corrente elétrica gerada por um estimulador que despolariza o neurônio motor e induz contrações musculares involuntárias, e já existem evidências científicas sobre sua aplicabilidade clínica [26][27][28] .…”
unclassified